Ecclesiological Background of G. B. Montini - Saint Paul VI. On the Occasion of his Recent Canonization - Berckholtz Benavides, Klaus (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2019)
A perhaps little-known aspect of the recently canonized Pope Paul VI is that, even before being elected Supreme Pontiff, he was an expert scholar of the Church, to whom he dedicated several of his writings. The most important characteristics of his ecclesiological approach are analyzed in this article, focusing attention on the years of his episcopal ministry in Milan. For this, his humanistic, philosophical and theological education is reviewed, as well as the most relevant authors who marked his ecclesiological perspective. It also offers a synthetic view of the main texts in which he addressed the mystery of the Church.
Keywords: Church; G. B. Montini; Saint Paul VI; 20th century; Archbishop of Milan